Chinese Herbal Medicines and Conventional Chronic Heart Failure Treatment for the Management of Chronic Heart Failure Complicated with Depression: A Systematic Review and Meta-Analysis. (22nd April 2020) - Yang, Peidan; He, Jun
Abstract : Background . Combination therapy with Chinese herbal medicines (CHMs) and conventional medical treatment (CMT) was proposed as a therapeutic strategy for chronic heart failure (CHF) patients complicated with depression. Therefore, we performed a systematic review and meta-analysis of randomized controlled trials (RCTs) to assess effects of this combination therapy on CHF complicated with depression. Methods . RCTs comparing the combination of CHMs and CMT to CMT were retrieved in seven electrical databases till March 30, 2019. The effective rate of cardiac function and Hamilton depression scale (HAMD) were marked as the primary outcomes. Left ventricular ejection fraction (LVEF) and Minnesota Living with Heart Failure Questionnaire (MLHFQ) were marked as the secondary outcomes. The methodological quality of eligible RCTs used the Cochrane bias risk assessment tool. Stata 13.0 and Review Manager 5.3 were preferred for synthesizing the results if the results were appropriate. Results . Thirteen RCTs enrolling 1022 subjects met the inclusion criteria. The majority of the retrieved RCTs were evaluated to be of low methodological quality. The pooled results of the meta-analysis showed that CHMs plus CMT group created better outcomes compared to CMT alone therapy, as evidenced by the fact that the overall effects of combination therapy strategy were significantly greater than the control group in increasing effective rate of cardiac function (risk ratio (RR) = 1.28; 95% CI: 1.16 to 1.42), in improving depressive symptoms (HAMD) (standard mean difference (SMD) = −1.31; 95% CI: −1.68 to −0.95) and quality of life (MLHFQ) (weighted mean difference (WMD) = −8.42; 95% CI: −10.08 to −6.76), in increasing LVEF scores (WMD = 5.33; 95% CI: 4.30 to 6.35). Conclusion . The combination of CHMs and CMT increased the effective rate of cardiac function and LVEF scores and reduced HAMD and MLHFQ scale scores, which was a potential therapeutic strategy that improved the management of CHF patients complicated with depression. Future trials were needed to verify the above results since abnormal heterogeneity and poor quality of literature have existed in the included studies.